Actuality of colloid chemistry in chemical education of students of medical and pharmaceutical faculty - Shyrykalova, A. O.; Grekova, A. V.; Burdina, Ya. F.; Sidelnykova, T. A. (Journal of Education, Health and Sport, 2019)
The article is dedicated to the one of the modern medical chemistry section named colloidal chemistry. It is not only component of basic chemical equation of future doctors and pharmacist, subject of medical and pharmacephtical scientific and experiment investigations but colloidal chemistry is the base of a modern and more promising direction of medicine called nanomedicine.